THE INFLUENCE OF DIFFERENCES STRATEGY, MARKET ORIENTATION, AND INNOVATION OF COMPETITIVE ADVANTAGES AND COMPANY PERFORMANCE (Empirical Study on Star Hotels in Semarang City) - Markus, Novita Lely; Raharjo, Susilo Toto; Mahfudz, Mahfudz (Master of Management Diponegoro University, 2018)
This research aims to examine and analyze the influence of differentiation strategy, market orientation, and innovation in an effort to build a competitive advantage for the performance of the company improves on star hotels in the city of Semarang. The respondents in this research are the Manager of star hotels in the city of Semarang, the size of respondents in filling in the questionnaire is 63 (sixty-three) people. However, for some reason, 22 (twenty-two) respondents are not willing to do the filling out the questionnaires which resulted in the final sample size is 41 (forty-one) respondents.in this case, the tool used in the study is the analysis of Partial Least Square (PLS). Prior to testing the researchers first tested the questionnaire by means of the validity test and reliability test. Test validity is to see the questionnaire is valid or not, and the reliability test is meant to see the questions distributed reliable or not to do further testing. The empirical findings indicated that the differentiation strategy has a significant positive effect on competitive advantage; innovation has a significant positive effect on firm performance.